USABILITY EVALUATION OF A MOBILE PHONE BASED BRAILLE LEARNING APPLICATION "MBRAILLE" - Nahar, Lutfun; Jaafar, Azizah; Sulaiman, Riza (Malaysian Journal of Computer Science, 2019)
The introduction and evaluation of Braille-learning tools are not receiving attention despite the need for talking books and Braille reading materials. As the Braille learning tools are very limited in developing countries, newly introduced tools and technological solutions need to be properly evaluated for implementation with the required improvements. The current study evaluated a smartphone-based interactive application â€œmBRAILLEâ€ for teaching early Braille-writing skills in English and Bangla. The mBRAILLE is developed to provide a cheap and affordable technology to the visually impaired (VI) students in Bangladesh. The application will help them learn Braille. A two-stage evaluation was performed in Bangladesh to determine the effectiveness of the application. The first stage of evaluation was performed with five school-aged VI children and five teachers from a blind school to determine the satisfaction level of the users while interacting with the application. This evaluation focused on 5 usability criteria, namely, learnability, memorability, efficiency, error, and satisfaction. After using mBRAILLE, participants evaluated the interfaces of the application through a specific questionnaire. Evaluation results showed that mBRAILLE meets the considered usability criteria, indicating that the interaction between application and users was on a desired level of satisfaction. Additionally, teaching ability of the application was evaluated by 5 real users in the second stage of evaluation, with a positive result. Therefore, given that the application is an effective tool to learn and teach English and Bangla Braille, it can be implemented in Bangladesh to assist VI students.